Opaque poetics in Salvador Plascencia’s The People of Paper - Riach, GK (Routledge, 2021)
This article reads Salvador Plascencia’s The People of Paper (2005) in dialogue with Édouard Glissant’s concept of “opacity”, an ethical and esthetic stance that values impeding comprehension. This novel’s opacity arises from various limiting mechanisms – linguistic, translational, and formal – which both invite and inhibit interpretation, and in so doing open up a space in which readers can think with the text. Bringing The People of Paper and Glissant’s thought together shows how Plascencia’s text thickens and complicates readerly engagement, and so increases the esthetic purchase of the novel. The People of Paper both invites and deflects the idea that esthetic experience might offer a route to understanding the social or that it provides the foundation of a more ethical relation with others. In parallel, Plascencia’s innovative use of the page and his invocation of an intertextual history of such innovation expands the scope of Glissant’s theory, by incorporating the physical medium of the book and the workings of genre history as components of an opaque poetics.